Effective SERS materials by loading Ag nanoparticles into poly(acrylic acid-stat-acrylamide)-block-polystyrene nano-objects prepared by PISA. (14th May 2021) - Demirci, Gokhan; Muszyńska, Julita; Cetinkaya, Onur; Filipczak, Paulina; Zhang, Yaoming; Nowaczyk, Grzegorz; Halagan, Krzysztof; Ulanski, Jacek; Matyjaszewski, Krzysztof; Pietrasik, Joanna; Kozanecki, Marcin
Abstract: Spherical nano-objects composed of poly(acrylic acid- stat -acrylamide)- block -polystyrene (P(AA- stat -Am)- b -PS) were prepared via polymerization induced self-assembly (PISA) and used as templates for the synthesis of hybrid Ag@P(AA- stat -Am)- b -PS. These well-defined hybrids were used as effective surface-enhanced Raman spectroscopy (SERS) supports for adenine detection as targeting molecule. Due to the presence of acrylamide units, the interactions between carboxyl groups, –COOH and AgNP were tuned, leading to the improvement of SERS effect in comparison to the system based on PAA– b -PS. SERS activity for Ag@P(AA56 - stat -Am19 )- b -PS375 (ratio 1:1) was 20 times higher (36x10 4 ) as compared to the reference system; PAA86 - b- PSt380 . Graphical abstract: Image 1 Highlights: (PAA- stat -PAm)- b -PS nanoobjects were prepared by PISA. They were used as templates for Ag nanoparticles synthesis. Ag@P(AA- stat -Am)- b -PS hybrids were used as effective SERS supports.